REPRODUCTIVE QUALITIES OF MIRGOROD BREED SOWS WHICH ARE CROSSED WITH BOARS OF MEAT TREND PRODUCTIVITY - Щербань, Т. В. (Scientific Progress & Innovations, 2014)
Mirgorod breed of pigs is regarded as the local vanishing breed; that is why search of the ways for its preserving is urgent. The comparative analysis of reproductive qualities’ indices of Mirgorod breed sows, which are purebred and crossed with specialized meat genotypes has been conducted in the article. Positive influence of Landrace breed boars on the reproductive capacity of Mirgorod breed sows has been proved; the negative effect on reproductive qualities as a result of crossing with the breed Pietrain and Large White of English selection has been shown.